PRICING IN PUBLIC PASSENGER TRANSPORT AND ITS DEPENDENCE TO RISK ALLOCATION - Kilianova, Katarina (Doprava a spoje, 2011)
The problem which deals with pricing in public passenger transport is discussed in this article. This problem is a reset of Regulation (EC) No 1370/2007 and its application to practise. Because of unpreparedness carriers, Slovak agreements of 2011 don't accept the principle of neutrality and the reasonable profit is specified as a percentage of costs. The price in public passenger transport should depend on risk which is carried by the operator or by the authority. This risk must be allocated to every agreement contracted in Europe. Because of the fact that Slovak republic isn't prepared to change pricing so the article states some manners of remuneration operators in Europe.